Correlation Between of Gadget Use to Sleep Patterns and Social Interaction in Students During COVID-19 Pandemic - Wulandari, Wulandari; Fitryasari , Rizki; Harmayetty, Harmayetty (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2023)
Introduction: The shift to online learning methods during the COVID-19 pandemic has significantly impacted the duration of gadget use. This change has been associated with health issues, including disrupted sleep patterns and altered student social interactions. This study explores the relationship between gadget use sleep patterns and social interactions among nursing students at Airlangga University during the pandemic. Methods: This research was conducted from January 21 to 23, 2022, using a correlational descriptive design with a cross-sectional approach. The study included 164 nursing students from Airlangga University, selected through simple random sampling. The independent variable was gadget use, and the dependent variables were changes in sleep patterns and social interactions. Instruments used included the Smartphone Addiction Scale, Pittsburgh Sleep Quality Index, and Social Interaction Anxiety Scale. Data were collected via a questionnaire and analyzed using Spearman's rho test, with significance set at <0.05. Result : Based on the results study, there was significant a relationship between gadget use and sleep patterns (p = 0.037, r = -0.163) and social interaction with results (p = 0.002, r = -236). Conclusion: Excessive use of gadgets, coupled with poor time management, can lead to social dysfunction in students, making them apathetic and less aware of their surroundings. Increased gadget usage correlates with reduced sleep quality and diminished social interaction. This research will serve as a valuable source of information and a reference for promoting health education and counseling related to gadget usage.